The Role of Islamic Economics in Promoting Sustainable Development in Developing Countries - Muhammad Ikram Idrus; Muhammad Ishlah Idrus (www.amertainstitute.com, 2025)
Sustainable development in developing countries faces serious challenges such as poverty, social inequality, and environmental degradation. Islamic economics, with its ethical principles such as the prohibition of riba (usury), the implementation of zakat (alms), and profit-sharing instruments (mudarabah/musharakah), offers a potential alternative framework to address these challenges. This article aims to analyze quantitative and qualitative evidence on the role of Islamic economics in accelerating the achievement of sustainable development goals (SDGs) in the context of developing countries. This study employs a literature review with a descriptive-analytical approach. Data were collected from various academic sources, reports from international institutions (such as the World Bank, IFSB, and UNDP), and official reports from Islamic financial institutions and zakat institutions in developing countries. The results of this study Islamic economics offers a viable and ethical paradigm for achieving sustainable development in developing countries. This study provides a compelling and growing body of evidence that Islamic Economics offers a coherent and practical framework for promoting sustainable development in developing countries. Its principles are theoretically aligned with the SDGs, and its instruments—ranging from ZIS and Islamic microfinance to green sukuk—demonstrate tangible impacts on social equity, economic inclusion, and environmental stewardship. However, realizing its full potential requires concerted efforts to address institutional, regulatory, and educational challenges. Future research should focus on longitudinal studies measuring the long-term impact of Islamic finance on SDG indicators and developing innovative financial products that fully integrate Islamic ethics with cutting-edge sustainability practices. This study also confirms that Islamic economics plays a significant and multifaceted role in driving sustainable development in developing countries, with contributions evident across all three pillars.